Design and Development of a Web-Based School Portal at SDN 060878 Using the Waterfall Method - Hafizhah Sufina Az-Zahra; Nova Mayasari; Andysah Putera Utama Siahaan; Eka Putra (CV. Hawari, 2026)
Current technological developments are encouraging the world of education to begin transforming into a digital-based system, which is one way to improve the effectiveness of administrative services and expand access to information in the school environment. The aim of this research is to build a website-based school portal that can be used to help deliver information while supporting academic and administrative activities. The system development process employed a waterfall approach, consisting of five phases: needs identification, system design, system development, implementation, and ongoing maintenance. The data used for this research was obtained through school observations, direct discussions with relevant school officials, and the collection of documentary data through photographs. The development of this school portal, the author hopes that the administration process and information delivery will be faster and well-documented, and can support the school digitalization process for information managers at SD Negeri 060878.